ANALISIS NILAI TAMBAH ABON SAPI PADA INDUSTRI RUMAH TANGGA MUTIARA HJ. MBOK SRI DI KOTA PALU - HM Syarif, Muh. Safri; Rauf, Rustam Abd.; Howara, Dafina (AGROTEKBIS, 2013)
The high added value that received byagroindustry entrepreneurs trigger increased competition, both in obtaining raw materials and in marketing of processing products. The role of agro industries in maintainthe primary product into processing products to increase the added value is required. One of the efforts made to increase added value mention previous wasto process the wet meatbeef cattle become cattle abon. This study aims to determine the added value obtained after the wet meat processed into cattle abon (shredded meat) at home industry MutiaraHj .Mbok Sri in Palu. Number of respondents were 5 people, including one person as home indutry leaders and four employees of home industry MutiaraHj.Mbok Sri. The added value of this study was the different between the value of output, the contribution of other inputs and raw material prices. The added value of home industry MutiarHj. Sri Mbok was Rp . 50416.67 kg. The total benefits expenditure of this cattle abon home industry MutiaraHjMbok Sri counted of Rp 46.305.78 by total margin of 91.84%.